Kampanie społeczne o tematyce zdrowotnej – analiza treści i form przekazów komunikacyjnych - Daszkiewicz, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Health and a healthy lifestyle are a subject of many social campaigns, the purpose of which is to build awareness, prevention, promotion of pro-health behaviors, help in the fight against disease and improve the quality of life of patients. The implementation of these goals is possible thanks to the construction of messages, the content of which results from the way of positioning, defining the direction of communication activities. Reaching the audience with the message requires choosing the appropriate forms of communication, which effectiveness depends on the analysis of the target market and the use of creative solutions. The article aims to identify the characteristics and forms of messages used in social campaigns regarding health and a healthy lifestyle. We used a collective case study of health-promotion campaigns awarded in the Social Campaign of the Year Competition organized by the Academy of Social Communication. The analysis covered the slogans, basic content, and forms of messages. We identified features that may influence the effectiveness of health campaigns. The analysis was made in the context of objectives, target audiences, and ways of positioning
Keywords: social campaigns; social marketing; health promotion; campaign message; marketing communication